Postmodernism of Remy Sylado's Menunggu Matahari Melbourne - Eva Dwi Kurniawan (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
The tendency of the spirit of postmodernism has led to all walks of life. Various forms and characteristics of postmodernism have also appeared in literary works. The novel Menunggu Matahari Melbourne by Remy Sylado is one of the novels that discusses the tendency of postmodernism in it. This research will set out as a starting point to explore the existence of postmodernism in the novel. The formulation of the problem that will be raised in this research is how are the forms of postmodernism in the novel Menunggu Matahari Melbourne by Remy Sylado? and how the forms of postmodernism are shown in the novel. The approach used in this study uses a postmodernist literary approach. The findings obtained are 1) enlivening the marginalized; 2) the breakdown of major narratives, 3) the tendency to world folds, and 4) unusual text aesthetics